Influence of diet supplementation with green tea extract on drug-metabolizing enzymes in a mouse model of monosodium glutamate-induced obesity - Boušová, Iva; Matoušková, Petra; Bártíková, Hana; Szotáková, Barbora; Hanušová, Veronika; Tománková, Veronika; Anzenbacherová, Eva; Lišková, Barbora; Anzenbacher, Pavel; Skálová, Lenka (European journal of nutrition, 2016)
PURPOSE: Consumption of dietary supplements with green tea extract (GTE) is popular for weight management, but it may be accompanied by various side effects, including interactions with drugs. The aim of the present in vivo study was to evaluate the effect of defined GTE (Polyphenon 60) in three dosage schemes on insulin, leptin and drug-metabolizing enzymes in obese mice. METHODS: Experimental obesity was induced by repeated s.c. application of monosodium glutamate to newborn mice. Green tea extract was administered in three dosage schemes in chow diet. The plasmatic levels of insulin and leptin were assayed using enzyme-linked immunosorbent assay. Enzyme activities and mRNA expressions of drug-metabolizing enzymes (totally 13) were analyzed in liver and small intestine using spectrophotometric and HPLC assays and RT-PCR, respectively. RESULTS: GTE-treatment decreased insulin and leptin levels. Eleven enzymes were significantly affected by GTE-treatment. Long-term administration of 0.01% GTE caused increase in the activity and mRNA level of cytochrome P450 3A4 (CYP3A4) ortholog in the liver as well as in the small intestine. Interestingly, short-term overdose by GTE (0.1%) had more pronounced effects on enzyme activities and mRNA expressions than long-term overdose. CONCLUSIONS: GTE-mediated induction of CYP3A4 ortholog, the main drug-metabolizing enzyme, could result in decreased efficacy of simultaneously or subsequently administered drug in obese individuals.
Keywords: Liver; Animals; Mice, Obese; Cytochrome P-450 CYP3A; Enzyme-Linked Immunosorbent Assay; rodina 2 cytochromů P450; Sodium Glutamate; vztah mezi dávkou a účinkem léčiva; Antioxidants; játra; rostlinné extrakty; Dietary Supplements; Leptin; Obesity; Mice; Tea; cytochrom P-450 CYP3A; Cytochrome P450 Family 2; messenger RNA; potravní doplňky; Insulin; myši; Cytochrome P-450 CYP2E1; myši obézní; RNA, Messenger; leptin; Catechins; Dose-Response Relationship, Drug; ELISA; cytochrom P-450 CYP2E1; obezita; Male; modely nemocí na zvířatech; Aryl Hydrocarbon Hydroxylases; antioxidancia; Green tea extract; Disease Models, Animal; Plant Extracts; Metabolic syndrome; zvířata; mužské pohlaví; inzulin; Drug-metabolizing enzymes; glutamát sodný; čaj; aromatické hydroxylasy